Chromium In Urban Soil-Plant-Water Ecosystems - Mondol, MN; Chamon, AS; Faiz, B; Elahi, SF (Journal of Bangladesh Academy of Sciences, 2014)
Heavy metal pollution is associated with public health concerns. The study was conducted at the vicinity of the Tejgaon industrial area (8 km2) adjacent to Dhaka City Corporation. To investigate the seasonal extent of soil-water ecosystems pollution with chromium discharged from the industries, municipality, and slums, and its transfer co-efficiency into plants or crops. Composite soil, plant and water were randomly collected from industrial sites by GPS guided sampling procedure during wet and dry seasons, processed, and analyzed. Soils were analyzed for particle size distribution (sand, silt and clay), pH, electrical conductivity (EC), total organic carbon, water-soluble, ammonium acetate extractable, DTPA extractable and total chromium. Plant samples were analyzed for total Cr concentration. Water samples were analyzed for pH, EC, and dissolved Cr concentration. During wet season, the average Cr concentration was 0.16, 0.72, 1.51 and 68 mg/kg, and in the dry season the concentrations were 6.60, 12.44, 23.1 and 248.3 mg/kg as water-soluble, NH4OAc and DTPA extractable and total, respectively. Total Cr concentration was 248.3 mg/kg, which was more than 2 times higher than the tolerable limit. Plant samples accumulated more and tolerated higher amounts of Cr during dry season. During dry season, more than 47% of water samples were found above the WHO standard level. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17558 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 173-187, 2013